Urgency of Indonesia to Establish a Comprehensive COVID-19 Pandemic Law: Lesson Learned from Singapore - Fauziah, Mastin Annisa Nur (Indonesian Comparative Law Review, 2021)
Indonesia, during the second wave of COVID-19 has become one of the country that was deemed to have had the highest COVID-19 cases and death rate similar to India, Iran, and Italy in 2020. Despite the low number of cases Indonesia currently have, the dismissive approach of the Indonesian government and the late response towards COVID-19 on the early days was some of the root of the issues. This tragedy could have been avoided if the Indonesian government act in a serious and efficient manner. This study seeks to create a solution or as a mirror for the Indonesian government in creating a comprehensive pandemic laws. Singapore, arguably have been successfully implementing the “living with COVID-19” Indonesia wished to achieve in mid-2020 during the “new normal” attempt. This study concludes that Indonesia could attain that standard under the condition that Indonesia have a strategic plan such as implemented by Singapore at the moment through gradual exit strategy and high vaccination rates. In preparing for the third wave, Indonesia could also mirror the pandemic laws application in Singapore in the early days where lockdown was stricter and penalty was not lax. This study hopes that if in the worst scenario Indonesia is attacked by third wave of COVID-19 cases, Indonesia will be ready to tackle such challenges by learning some measures implemented by the Singapore government.